Surprise! : from CEOs to Navy SEALs : how a select group of professionals prepare for and respond to the unexpected - Baiocchi, Dave; Fox, D. Steven (Rand Corporation monograph series., 2013)
This report relates what professionals believe creates surprise, how they respond to it, and how the effects of surprise can be mitigated. To understand how different professions respond to surprise, RAND researchers developed a framework that categorizes professionals' responses to surprise in terms of the time available to respond and the level of chaos in the environment, then conducted discussions with representatives from 13 different professions, including former ambassadors, chief executive officers, military personnel, and physicians. RAND observed that the interviewees all used common coping strategies, such as relying on past experience and trying to reduce the level of chaos in the environment. However, there were also important differences in the responses taken by different types of professionals: "strategists" (e.g., CEOs and foreign service officers) focused more on controlling anger and ego, and communicating and coordinating with others, while "tacticians" (e.g., medical practitioners and SWAT team members) -- who typically have a shorter response time -- focused more on controlling panic and buying time. The report concludes with recommendations on how practitioners can better prepare for and respond to surprise.